2004
DOI: 10.1093/eurheartj/ehi033
|View full text |Cite
|
Sign up to set email alerts
|

B-type natriuretic peptide: a novel early blood marker of acute myocardial infarction in patients with chest pain and no ST-segment elevation

Abstract: BNP is a useful adjunct to standard cardiac markers in patients presenting to the emergency department with chest pain and no ST-segment elevation, particularly if initial CKMB and/or troponin-I are non-diagnostic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
76
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(81 citation statements)
references
References 35 publications
3
76
1
1
Order By: Relevance
“…Thus, higher baseline levels of NT proB-NP was directly associated with age i.e. patients with NTproBNP > 258pg/ml were older (median age 68 yrs).These finding were consistent with earlier studies by Sadanandan S. et al, Morrow DA et al and Bassan R et al, who also reported that higher level of BNP was seen in older patients (10,11,12).Out of 72 cases NSTEACS was seen in 56 (77.7%) of cases and UA was seen in 16(22.3%) of cases. Both UA/NSTEACS were seen predominantly in males.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Thus, higher baseline levels of NT proB-NP was directly associated with age i.e. patients with NTproBNP > 258pg/ml were older (median age 68 yrs).These finding were consistent with earlier studies by Sadanandan S. et al, Morrow DA et al and Bassan R et al, who also reported that higher level of BNP was seen in older patients (10,11,12).Out of 72 cases NSTEACS was seen in 56 (77.7%) of cases and UA was seen in 16(22.3%) of cases. Both UA/NSTEACS were seen predominantly in males.…”
Section: Discussionsupporting
confidence: 90%
“…This finding was consistent with earlier studies by Bassan R et al Lindahl et al and Heeschen. (12,(14)(15). Diabetes, hypertension smoking and dyslipedemia were seen more in NSTEACS group than in UA patients but difference was not statistically significant (Table-3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Myocardial cell death (and the release of its necrosis markers) is a final event (3). BNP was found to be very useful in the emergency department for the diagnosis of acute MI in patients with chest pain, particularly when standard cardiac markers are non-diagnostic (14). In fact, BNP has been found to increase in the setting of MI with peak levels occurring 14 to 40 h after the ischemic event (4).…”
Section: Discussionmentioning
confidence: 99%